1969
DOI: 10.1136/gut.10.11.924
|View full text |Cite
|
Sign up to set email alerts
|

Regional enteritis leading to carcinoma of the small bowel

Abstract: SUMMARY A case of carcinoma of the small bowel intimately associated with long-standing regional enteritis (Crohn's disease) is described. Sixteen similar cases reported in the literature are briefly reviewed. This neoplasm presents at a younger age than other small bowel carcinomas and there seems little doubt that it is causally related to the inflammatory bowel lesion. He was anaemic (haemoglobin 10-3 g/100 ml, electrolytes within normal limits); no intestinal pathogens were isolated; serum proteins, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1971
1971
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…That this age difference and distribution simply reflect the group sampled is unlikely. A comparable incidence of other smallbowel malignant tumours would be expected, but only 3 cases have been reported-a lymphosarcoma in this series and 2 cases of reticulum-cell sarcoma (Hughes, 1955;Wyburn-Mason, 1968). There is Vol.…”
Section: Discussionsupporting
confidence: 53%
“…That this age difference and distribution simply reflect the group sampled is unlikely. A comparable incidence of other smallbowel malignant tumours would be expected, but only 3 cases have been reported-a lymphosarcoma in this series and 2 cases of reticulum-cell sarcoma (Hughes, 1955;Wyburn-Mason, 1968). There is Vol.…”
Section: Discussionsupporting
confidence: 53%
“…There is a suggestion, therefore, that the part of the bowel most affected in coeliac disease is also the most common site for carcinoma. Yet this evidence is much less striking than it is in regional enteritis, where many more small bowel carcinomas have been described and nearly all of them have been in the ileum (Wyatt, 1969). Furthermore, in regional enteritis, the mean age at diagnosis of malignancy, about 43 years, is also younger.…”
Section: Discussionmentioning
confidence: 95%
“…The granulomatous character of the typical bowel lesions shows a resemblance to sarcoidosis and some patients with Crohn's disease have been shown to react in weak but characteristic manner to a Kveim antigen by skin testing (Mitchell and Rees, 1970) and by inhibition of macrophage migration in the presence of this antigen (Willoughby and Mitchell, 1971). Wyatt (1969), in a study of reported cases of adenocarcinoma of the small bowel complicating Crohn's disease, found 17 examples and noted that the mean age of occurrence was almost 20 years earlier than would be expected from the available world figures. A similar conclusion was reached by Mottet (1971) and by Papp and Pollard (1971), ponderance of tumour involvement in the ileum with Crohn's disease as compared with a more frequent distribution in the duodenum and jejunum in the absence of Crohn's disease.…”
mentioning
confidence: 99%